SAT0624 Predictors of Persistence of Power Doppler Ultrasound Synovitis in Rheumatoid Arthritis Patients in Clinical Remission. (9th June 2015) - Filippi, N.; Lukas, C.; Morel, J.; Combe, B.; Mouterde, G.
Abstract : Background: Ultrasound (US) is a sensitive tool for the evaluation of joint inflammation in patients with rheumatoid arthritis (RA), and can detect synovitis even when clinical remission is present [1]. Predictors of persistence of such subclinical power Doppler ultrasound (PDUS) synovitis, like potentially severity of the disease, concomitant treatments, or duration of the remission, remain undetermined. Objectives: The aims of this study were: (1) to assess the proportion of patients with persistent PDUS synovitis in a cohort of patients with RA in clinical remission (DAS28-ESR<2.6 and without clinically active synovitis); (2) to determine predictors of persistence of PDUS synovitis in these patients. Methods: RA patients fulfilling 2010 ACR-EULAR classification criteria, treated with DMARDS or biologic and in clinical remission (DAS28-ESR<2.6 and without clinically active synovitis, i.e. no joint showing both pain and swelling), were included in this transversal study. Following data were collected: clinical and biological characteristics of arthritis, socio economic factors, and radiographs of hands, wrist and feet. A standard US examination on 40 joints for the presence of synovial hypertrophy and power Doppler signal was performed by an independent investigator blinded to clinical data. A subclinical US synovitis was defined by the presence of a power Doppler signal ≥1 in at least one joint. Logistic regression was performed to evaluate the association between subclinical US synovitis and baseline variables at the patient level. The reliability was evaluated with intraclass correlation coefficients (ICCs) based on independent assessments of 30 patients by two investigators. Results: The 103 patients included had a mean (standard deviation) age of 61 years (11.1), mean disease duration of 9.41 years (8), a mean duration of remission of 11.1 months (15). 66% and 70.9% of the patients were rheumatoid factor and anti-CCP antibody positive respectively. The mean DAS28-ESR was 1.01 (0.54) and 55.3% of the patients had erosive disease. 59.2% received methotrexate, 59.9% biologic treatment and 11.7% corticosteroids. Inter-observer reliability of assessment of synovial hypertrophy and PD signal were very good (ICC=0.954 and 0.985 respectively). Baseline clinical characteristics and US findings were similar whatever the duration of remission (<6 months, n=56 and ≥6 months, n=47). PD signal ≥1 was detected in at least one joint in 60 patients (58.3%). In multivariate analysis, presence of anti-CCP (OR=3.05 [95% CI 1.19-7.83], p=0.020), was predictor of persistence of PDUS synovitis ≥1, whereas current smoking was negatively associated (OR=0.23 [95% CI 0.07-0.72], p=0.012). The duration of the remission was not associated with PDUS synovitis after adjustment in this cohort. Conclusions: Our results suggest that RA patients in clinical remission are more likely to have persistence of PDUS synovitis if they have anti-CCP antibodies. Current smoking appears to be a protective factor in this cohort, which might potentially be due to vasoconstriction induced by tobacco. References: Saleem B, Brown AK, Keen H, et al. Ann Rheum Dis 2011;70(5):792-798. Disclosure of Interest: None declared